Finance and Development, June 1966. (Finance and Development; Finance and Development ;, 1966)
This paper discusses the study on development planning conducted by a small group within the World Bank. The study reveals that most countries not only encounter the same planning problems, they make the same mistakes. The paper highlights that although most countries with development plans have not succeeded in carrying them out, some countries without national development plans or national planning agencies have been developing rapidly. The paper also highlights that the lack of government support is the prime reason why so few development plans are carried out.